Incidence of Readmission in Patients in Sulaimani Emergency Hospital - H Faraj, Faruk; Y Ali , Authman (Diyala Journal of Medicine, 2019)
Background:Readmission after hospitalization is a preventable experience which can impose huge costs on the patients and the health care systems. Studies have reported that readmission of patients within 30 days following discharge is quite common and associated with some clinical and nonclinical factors. Mental and behavioral health issues, alcohol-related disorders, pregnancy, diabetes, schizophrenia, and mood disorders have been reported as the commonest conditions that can cause readmission. Research has also stated that patient readmission can show low quality of health care services. Objective: To assess the incidence of patients who had been readmitted to emergency room in Sulaimani Emergency Hospital during three consecutive months. Patients and Methods:The present prospective study which was carried out on 126 readmitted patients who were selected from 3264 patients who had referred to Sulaimani Accident & Emergency Hospital in Kurdistan Region of Iraq from (1st. Jun 2018 ) to ( 31st.Aug. 2018 ) . A researcher-designed checklist was used to collect the required data. The collected data were analyzed through descriptive statistics using Statistical Package for Social Sciences version 22.0, and the results were presented as frequencies and percentages in tables. Results: The results of the present study revealed that the hospital readmission rate was lower among the patients older than 50 years. Also, female patients accounted for a larger population of readmitted patients than the males. There was no significant association found between gender and readmission. Epigastric and abdominal pains were the most frequent symptoms and presentations observed at readmission. In addition, associated medical diseases and surgical procedures were found to have outstanding effect on readmission. The most common detected disorders among the readmitted patients were suspected acute appendicitis and acute pancreatitis. In addition the type of medical intervention was found to have a remarkable effect on the rate of readmission. A significant relationship was observed between the observed clinical presentations and the readmitted patients’ age, occupation, and marital status. Also, the readmitted patients’ past surgical history and their age, gender, occupation, and marital status were significantly correlated. Conclusion: Hospital readmission was found to be common among patients who had associated medical diseases, surgical procedures, suspected acute appendicitis, and acute pancreatitis; therefore, such patients need to be provided with more careful care and proper medical interventions in order to prevent or reduce readmission rate and consequently cut costs. Moreover, while admitting and readmitting patients, their age, gender, marital status, and occupation need to be taken into close account because these variables are effective in their clinical presentation and correlated with their past surgical history. DOI:https://doi.org/10.26505/DJM.17024780711